Perbandingan Alternatif Model Peremajaan Kakao dengan Tanaman Sela di Kabupaten Pesawaran Provinsi Lampung - Putri, Tursina Andita; Yanuar, Rahmat; Rifin, Amzul; Sarianti, Tintin; Herawati, Herawati (Politeknik Negeri Lampung., 2024)
Cocoa replanting with intercrops is a strategy for sustainable cocoa development. Cocoa replanting is expected to impact productivity and production quality and increase selling prices positively. However, there are still many farmers who are reluctant to replant due to concerns about losing sources of income and financing difficulties. The study analyzed the cost and income structure of various replanting models. Based on the survey, there were 88 cocoa farmers as respondents, 51 who replanted and 37 who did not. Through the analysis of cost and income structures, it is known that replanting cocoa can be a rational option for farmers who want to increase their income because replanting can increase the productivity of cacao. In addition, the income from the intercrops has also been shown to replace the income of the cocoa lost at the time of the replanting. Analyzing the partial profit balance shows that bananas and chili are profitable crops to plant as intercrops on cocoa groves when replanting. For farmers who plant bananas as an intercrop, the income from bananas can cover unloading costs, seed costs and cocoa planting costs within one year